2004
DOI: 10.5194/npg-11-463-2004
|View full text |Cite
|
Sign up to set email alerts
|

Detecting nonlinearity in time series driven by non-Gaussian noise: the case of river flows

Abstract: Abstract. Several methods exist for the detection of nonlinearity in univariate time series. In the present work we consider riverflow time series to infer the dynamical characteristics of the rainfall-runoff transformation. It is shown that the non-Gaussian nature of the driving force (rainfall) can distort the results of such methods, in particular when surrogate data techniques are used. Deterministic versus stochastic (DVS) plots, conditionally applied to the decay phases of the time series, are instead pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…We are currently investigating how nonlinearities in the processes that govern sandbar behavior express themselves in time series of sandbar positions. Work of Laio, Porporato, Ridolfi, and Tamea (2004) on rainfall-runoff time series, for instance, demonstrates that the presence of nonlinear processes in a system does not necessarily imply that time series from specific variables in this system are nonlinear themselves.…”
Section: Discussionmentioning
confidence: 99%
“…We are currently investigating how nonlinearities in the processes that govern sandbar behavior express themselves in time series of sandbar positions. Work of Laio, Porporato, Ridolfi, and Tamea (2004) on rainfall-runoff time series, for instance, demonstrates that the presence of nonlinear processes in a system does not necessarily imply that time series from specific variables in this system are nonlinear themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Ref. 37 showed that DVS plots can effectively be employed when time series is noisy, short, and non-Gaussian; these features assure DVS as an ideal option for exploiting the nonlinear behavior of ambient noise. This technique aids in overcoming the liability faced by traditional nonlinear methods, such as correlation dimension and Lyapunov exponents.…”
Section: Nonlinear Predictionmentioning
confidence: 99%
“…Though it is robust towards non-Gaussianity, it is difficult to distinguish between a nonlinear non-Gaussian system with a linear Gaussian system, since the possible nonlinearities tend to be dominated by the stochastic component. Furthermore, it is not a real statistical test "since no test statistics are produced which allows a unequivocal acceptance or rejection of the null hypothesis of linearity" (Laio et al, 2004). Laio et al (2004) also showed that a surrogate data set generated from a linear decay system with non-Gaussian shot noise (see Eq.…”
Section: Surrogate Data Testmentioning
confidence: 99%
“…Furthermore, it is not a real statistical test "since no test statistics are produced which allows a unequivocal acceptance or rejection of the null hypothesis of linearity" (Laio et al, 2004). Laio et al (2004) also showed that a surrogate data set generated from a linear decay system with non-Gaussian shot noise (see Eq. 3 below) appeared significantly different than an original data set and tested for reversibility using a simple third order statistic.…”
Section: Surrogate Data Testmentioning
confidence: 99%
See 1 more Smart Citation